Pengaruh Penghalang Pada Intake Manifold Terhadap Emisi Gas Buang Motor Injeksi 125cc - Gabrie Umar Bakti Mulana; Khambali Khambali; Yuniarto Agus Winoko (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze the effect of barriers on standard intake manifolds on exhaust emissions in 125cc capacity injection motors. The applied barrier is expected to modify the intake air flow, which has an impact on the combustion process and the resulting exhaust emissions. The method used includes testing exhaust emissions with variations in the use of barriers under several engine conditions, including different engine speeds. The results show that the use of barriers can affect CO, HC, and O2 emission levels, with certain variations indicating changes in combustion efficiency. The conclusion of this research is that the selection of the right barrier diameter and intake manifold shape can contribute to the reduction of exhaust emissions of 125 cc injection motorcycles. The results of this study are expected to be a reference for the automotive industry in designing a more environmentally friendly intake manifold system.